The distribution of brown trout (Salmo trutta L.) in streams in southern Sweden. - Eklöv, Anders (Department of Ecology, Lund University, 1998)
This thesis examines the effect of water quality, habitat and species interactions on the occurrence and abundance of stream fishes in southern Sweden. I found that improvements in water quality between the 1960s and 1990s have led to recolonization of streams by brown trout (Salmo trutta L.), stone loach (Barbatula barbatula L.) and eel (Anguilla anguilla L.). The response was greatest for brown trout and was best explained by increased dissolved oxygen concentrations. The occurrence of other species, specially the nine-spined stickleback (Pungitius pungitius L.), ide (Leuciscus idus L.) and brook lamprey (Lampetra planeri L.) decreased between the 1960s and 1990s. The decrease was greatest for nine-spined stickleback and was related to the increase in sites with trout, indicating that nine-spined stickleback may be sensitive to predation or competition. In-depth studies of brown trout showed that physical habitat influenced trout densities, especially for 0+ trout, where high densities were associated with narrow streams and with cover. Field manipulations of cover indicated that submerged macrophytes supported high 0+ trout densities in small and medium-sized streams, where other types of instream cover were scarce, and therefore may be especially important in canalized streams. Interspecific and intraspecific interactions also affected trout densities as well as trout behaviour and growth. In a field survey, trout density was inversely related to the abundance of piscivores. Moreover, experiments in artificial stream channels showed that the presence of piscivores could cause habitat shifts and decrease food intake by brown trout. Other experiments in these stream channels showed that intraspecific size-class competition in trout reduced food intake by smaller individuals. Intraspecific competition also seems to explain variation in length of 0+ trout in the field as body length was inversely correlated with trout density, indicating that density may affect trout growth.